Debunking the myth of money in a multigenerational workforce - Lee, S.T.; Jayasingam, S.; Mohd Zain, K.N. (2014)
Money is a common denominator used to purchase goods and services worldwide. People work for money to survive. Organizations spend millions to pay the salaries of their employees with the hope for better performance in return. Undeniably, money influences people's lives to a certain extent. However, can it motivate every individual or is there a misguided perception that everyone is money driven? This question is becoming pertinent especially with Baby Boomers, Generation X, and Generation Y entering the workforce and transforming the workforce demographics. It is no longer a homogeneous group.